Application effect of the online and offline mixed education mode in nursing practice based on the SMCR communication model - Chen, Qian; Jin, Yanhong; Zhong, Lixia; Li, Yingying; Fu, Li; Zhang, Weiwei; Xu, Qiuying (Frontiers in Medicine, 2024)
Objective To explore the application effect of the online and offline mixed teaching mode in nursing practice teaching based on the Source Message Channel Receiver (SMCR) communication model. Methods By using the convenience sampling method, 15 nursing students who practiced their internship in the Department of Critical Care Medicine at Beijing Friendship Hospital affiliated to Capital Medical University for 4 weeks, from 1 April 2022 to 31 December 2023, were selected as the experimental group. A total of 16 nursing students who practiced in the same hospital in 2021 were selected as the control group. The control group used traditional teaching mode for teaching, and the experimental group used the online and offline teaching mode for teaching. The theoretical and practical achievements, competency, and teaching satisfaction of the two groups of nursing students were compared and analyzed after the internship. Results The theoretical knowledge, operational performance, competence of the nurses, and satisfaction with the teaching in the experimental group were higher than those of the control group (P < 0.05). Conclusion Based on the SMCR communication model, exploring the online and offline mixed teaching mode plays an important role in the teaching process of nursing practice, which can not only effectively improve the comprehensive performance of nursing students but also help to improve their satisfaction with teaching and has a positive impact on the cultivation of high-quality nursing talents.